Comparison of young and elderly patients with rectal cancer in terms of prognostic factors and clinical features: A retrospective analysis - Tokgoz, Serhat; Saydam, Mehmet; Olcucuoglu, Engin; Kaya, Oskay (Annals of Medical Research, 2021)
Aim: Rectal Carsinoma (RC) has considerable morbidity, mortality, and highly operational costs. RC is generally known as a disease of the elderly especially beyond the age of 50 years. Nevertheless, the incidence of RC in younger adults (aged ≤50 years) has been increasing widely. Our aim is to evaluate the clinical and histopathological features of the patients under and over 50 years with RC and their contribution to prognosis.Material and Methods: Patients with RC who were treated in our clinic included in the current retrospective designed study, and their data collected including demographics, clinical presentations, histopathological features, disease characteristics, treatment received or not, survival and outcomes. Their variables were compared statistically.Results: This study included 187 RC patients from our General Surgery Clinic. Median age at diagnosis was 62 years (min:26-max:88). Lack of perineural invasion significantly affected disease-free survival and overall survival in general (p 0.035-p 0.001). High grade of tumor variable was statistically significant in favor of ≤ 50 years group (p: 0.0082).Conclusion: RC in young-onset is related with poor prognostic factors such as aggressive histological features, high grade and stage tumors. Clinicians should pay more attention and interest to the symptoms and sings of the bowel in younger patients and should not hesitate to perform screening tests such as blood test, or especially rectosigmoidoscopy, etc to be initiate early diagnosis and further treatment.
Keywords: Prognosis; rectal cancer; young-onset colorectal cancer